2022
DOI: 10.21203/rs.3.rs-1314420/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Authentication of Microplastic Accumulation in Customary Fruits and Vegetables

Abstract: The environment has become a major source of plastic pollution. Microplastics have been well documented in aquatic ecosystems as an increasing pollutant of worldwide relevance, but little is known about their effects on the terrestrial environment, particularly in agroecosystems. Researches have recently proven that microplastics can affect human health and are found in human organs and tissues. In this present study, two different types of fruits like grapes (Vitis vinifera) and banana (Musa paradisiaca), veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Table 2 showed that MPs contamination in potato samples in Pujon Kidul (0.05 particles g -1 ) was higher than Sumber Brantas (0.02 particles g -1 ) and Ngadas (0.03 particles g -1 ). These findings supported previous research, where MPs contamination in potatoes had been reported in the Ulungur River basin in Qinghe County, Altay, Xinjiang, China [28]; Tiruchirapalli -Trichy, Tamil Nadu, India [29], Catania city, Sisilia, Italy [30], and Muğla, Southern Western of Turkey [31]. MPs were found in potatoes produced in Pujon Kidul because the land used to grow potatoes had been contaminated with MPs in the amount of 0.03 particles g -1 .…”
Section: Abundancesupporting
confidence: 92%
“…Table 2 showed that MPs contamination in potato samples in Pujon Kidul (0.05 particles g -1 ) was higher than Sumber Brantas (0.02 particles g -1 ) and Ngadas (0.03 particles g -1 ). These findings supported previous research, where MPs contamination in potatoes had been reported in the Ulungur River basin in Qinghe County, Altay, Xinjiang, China [28]; Tiruchirapalli -Trichy, Tamil Nadu, India [29], Catania city, Sisilia, Italy [30], and Muğla, Southern Western of Turkey [31]. MPs were found in potatoes produced in Pujon Kidul because the land used to grow potatoes had been contaminated with MPs in the amount of 0.03 particles g -1 .…”
Section: Abundancesupporting
confidence: 92%
“…Ref. [ 59 ] analyzed the presence of microplastics in fruits (grapes and banana) and vegetables (brinjal and potato) samples taken from different markets in Trichy, Tamil Nadu (India) and reported the occurrence of microplastics of 2 and 10 µm size in fruits and 2 and 10 µm size in vegetables, respectively. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the beakers were left to dry in an oven set at 60 °C for 24–48 h. The dried samples were pulverized using a sterilized steel-made blender. Given the lack of a standard international protocol in the literature for the extraction of microplastics from fruits and vegetables, the methods reported by [ 65 ] modified by [ 59 ] was applied in this study. Accordingly, 5 g of dried powdered fruit and vegetable samples were weighed and placed into glass centrifuge tubes with 50 mL capacity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation